2007
DOI: 10.1520/gtj100164
|View full text |Cite
|
Sign up to set email alerts
|

Representative Elementary Volume Analysis of Sands Using X-Ray Computed Tomography

Abstract: The concept of a representative elementary volume (REV) provides an effective means of developing macroscopic measures in the description of granular materials. However, due to the difficulties associated with the measurement and characterization of granular microstructure the existence and size of an REV has remained largely conjectural. This study presents a systematic method to examine the characteristics of the REV using X-ray computed tomography images. The 3-D images of spherical glass beads, Silica sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 15 publications
10
36
0
Order By: Relevance
“…The REV chosen in this work has a size of 2·9D 50 , which is consistent with the literature for spherical/sub-spherical uniform assemblies (e.g. Razavi et al, 2006). It should be mentioned that the limited amount of breakage did not cause the D 50 to change (as can be seen in the following sections), and so in this paper D 50 will refer to both initial and final mean particle size.…”
Section: Porosity Distributionsupporting
confidence: 54%
“…The REV chosen in this work has a size of 2·9D 50 , which is consistent with the literature for spherical/sub-spherical uniform assemblies (e.g. Razavi et al, 2006). It should be mentioned that the limited amount of breakage did not cause the D 50 to change (as can be seen in the following sections), and so in this paper D 50 will refer to both initial and final mean particle size.…”
Section: Porosity Distributionsupporting
confidence: 54%
“…This study used the 225-keV micro-focused source to achieve enhanced resolution. 18,19 The CT scanning involved several steps: placing the specimen on the rotary stage, initiating the data acquisition from the work station, recording X-ray intensities before and after penetrating the specimen while rotating the specimen at small angles, collecting CT numbers over a full revolution, and analyzing CT numbers 19 to return sinograms of each slice.…”
Section: Glassy Statementioning
confidence: 99%
“…This result agrees with the values reported for granular materials. 14) However, this normalization is done with respect to the initial microstructure, which completely disappears during sintering.…”
Section: Relative Density Specific Surface Area and Sintering Stressmentioning
confidence: 99%
“…Recent advances in X-ray microtomography 12) and focused ion beam-scanning electron microscopy 13) have opened the door for observation of detailed microstructural evolution during sintering, and provides an opportunity to analyze the RVE from the knowledge of microstructure experimentally. In the field of particle packing, for example, Razavi and coworkers 14) reported that the concept of RVE provides an effective means of developing macroscopic measures in the description of granular materials. The RVE size has been determined for electrodes of a Li-ion battery 15) and solid oxide fuel cell.…”
Section: Introductionmentioning
confidence: 99%